Pelaku Pemalsuan Keterangan Bebas Covid-19 Oleh Anak Buah Kapal KM Cantika 99 - Clieverd Jery Tasane; Juanrico Alfaromona Sumarezs Titahelu; Erwin Ubwarin (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The danger of the COVID-19 pandemic has made the Minister of Health set a rapid test as a requirement for travellers. However, rapid test counterfeiting is still being carried out today.Purposes of the Research: To find out the criminal threat against the perpetrators of forgery of Covid-free information documents.Methods of the Research: This research is empirical juridical. Where the legal materials used rely on primary and secondary data.Results of the Research: The results of the study show that the crime of forgery of letters as referred to in article two hundred and sixty-three paragraph one of the Criminal Code was found on Thursday, August 20, 2020 at around 18:00 Wit at the port of Slamet Riyadi Ambon, in the form of fourteen a sheet of laboratory examination results, the letter was made by the suspect Viona M Noya same as Vio at the request of the suspect Izac Siwalette alias Izac which was intended as a sailing requirement for KM crew. Cantika Lestari 99 with the aim of East Seram.